PENINGKATAN PEMERATAAN DISTRIBUSI AIR BERSIH DI DUSUN KAJA-KAUH DESA SUDAJI DENGAN PENERAPAN TANGKI PELEPAS TEKAN - Suarda, M.; Suputra, I G.N.O.; Wirawan, I K.G.; Suweden, I N.; Sucipta, M. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Kaja-Kauh sub-village of Sudaji village located on hilly area, with a population of 231 households (1,155 people). The residents have been able to enjoy a clean water system since 2015 owing to the rotary international aid. Considering that the topography of the Kauh-Kaja sub-village is very steep, the distribution of water from the reservoir to the residential population is not evenly distributed. Resident whose home is located within the low level is getting water with a high pressure even its pipe until broke while residing at the higher level is difficulty in obtaining water. To overcome this problems it is the distribution of water in the Kaja-Kauh sub-village divided into three zones, namely up-zone, Middle-zone, and down-zone. In the lower-zone (elevation difference is more than 80 meters) has been installed a tank so that the distribution pipes in these areas is not broken. The pressure release tank has the benefit that it can reduce excessive (high) water pressure in the down-zone which can break pipes and damaging faucets of home connections. Furthermore, the pressure release tank system can create a more equitable distribution of water flow, especially the water flow to in the upper zone and becoming a better and smoother.